Compositional, Sensory and Quality Parameters of Chicken Patties Prepared with Carrots - Patel, Vaibhavi V.; Nayak, Jitendrakumar B.; Bhavsar, Prakrutik P.; Anjaria, Pranav A.; Brahmbhatt, Manoj N.; Parmar, Bhupendrakumar C.; Chaudhary, Jeetendrakumar H.; Soni, Manasi M. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
A study was undertaken to determine the effect of the incorporation of grated carrot in chicken patties. Chicken patties were  prepared by replacing lean meat with grated carrot at 3 levels, i.e., 10, 15, 20 %. The three treatments along with control were  evaluated for physico chemical properties, sensory evaluation and β-carotene estimation. Each experiment was repeated four times.  There was a significant increase (P
Keywords: Beta-carotene; Chicken meat; Chicken patties; Compositional; Functional foods; Sensory